Operating methods for mining in Peru median - de la Cruz, Estanislao (2012)
In Peru we have mineral deposits on the coast and in the highlands (Peruvian Andes), where you can find mineralization as veins, strata and bodies. Mining companies according to the type of deposit and some criteria choose the method of exploitation. By production volume, can be large mining, medium mining, small-scale and artisanal mining. Following the independence of Peru, nearly all the mines have been abandoned because workers were natural (Indians) of the Inca Empire, who were enslaved by invaders (Spanish) who worked with labor at no cost. When they wanted to restart mining operations, no pawn mine wanted to go to that "go to the mine was going to die." Until the rulers of the time (1895) offered many advantages to foreigners so they can exploit mines in Peru, reason comes to Peru in 1905 an American company in 1915 comes to form the Cerro de Pasco Corporation, which operated until 1974, when it was nationalized. This company implements technologies operating in six major mining units located in the central region of Peru, with mining professionals, geologists and chemists generally requirement that small and medium mining, migrate with the Know How and thus acquired techniques were implemented Mid-level and small-scale mining in Peru, which is now known as upward and downward cutting and filling, cut reduction, block caving and training of cadres or woodwork.